Bacteraemia Is Associated with Increased ICU Mortality in the Postoperative Course of Lung Transplantation - Alexy Tran-Dinh; Marion Guiot; Sébastien Tanaka; Brice Lortat-Jacob; Enora Atchade; Nathalie Zappella; Pierre Mordant; Yves Castier; Hervé Mal; Gaelle Weisenburger; Jonathan Messika; Nathalie Grall; et al. (MDPI AG, 2022)
We aimed to describe the prevalence, risk factors, morbidity and mortality associated with the occurrence of bacteraemia during the postoperative ICU stay after lung transplantation (LT). We conducted a retrospective single-centre study that included all consecutive patients who underwent LT between January 2015 and October 2021. We analysed all the blood cultures drawn during the postoperative ICU stay, as well as samples from suspected infectious sources in case of bacteraemia. Forty-six bacteria were isolated from 45 bacteraemic patients in 33/303 (10.9%) patients during the postoperative ICU stay. Staphylococcus aureus (17.8%) was the most frequent bacteria, followed by Pseudomonas aeruginosa (15.6%) and Enterococcus faecium (15.6%). Multidrug-resistant bacteria accounted for 8/46 (17.8%) of the isolates. The most common source of bacteraemia was pneumonia (38.3%). No pre- or intraoperative risk factor for bacteraemia was identified. Recipients who experienced bacteraemia required more renal replacement therapy, invasive mechanical ventilation, norepinephrine support, tracheotomy and more days of hospitalization during the ICU stay. After adjustment for age, sex, type of LT procedure and the need for intraoperative ECMO, the occurrence of bacteraemia was associated with a higher mortality rate in the ICU (aOR = 3.55, 95% CI [1.56-8.08], p = 0.003). Bacteraemia is a major source of concern for lung transplant recipients.